Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content: 1. Employing Artificial Intelligence in Developing Professional Development Programs for Teachers in the Sultanate of Oman in Accordance with Transformational Leadership Standards Mr. Ali Hamad Al-Buraiki, Dr. Youssef Nait Belaid 2. A Proposed Framework for Implementing Kaizen in Saudi Public Education Schools in Light of Vision 2030 Ms. Maryam Hamdan Al-Enazi 3. The Degree of Pracicing Leadership Skills among Kindergarten Teachers in Dawadmi Goverment from Their Point of View and Its Relationship to Some Variables Ms. Al-Jawhara Mardas Al-Mutairi,Ms. Nuha Mishaan Al-Shammari, Ms. Atheer Saad Al-Manjoumi 4. The Impact of Collaborative E-Learning on the Learning Motivation of Female Doctoral Students: A Case Study of Students in the Course on Employing Technology in Education Prof. Saida Jaser Affouneh,Ms. Eman Omar Drawshi,Ms. Areej Helmi Rabi,Ms. Reem Hani Zoubi,Ms. Sajida Sobhi Miari,Ms. Salwa Fawze Salame,Ms. Sana Fwaz Drawshy,Ms. Suheir Huleihel Nassar,Ms. Sireen Mahmood Azem,Ms. Sabrin Nor Drawshi,Ms. Safa Abdel-Kareem Asadi,Ms. Najwa Zeed Dabbah,Ms. Hiba Hasan Rabah, Ms. Wafika Ebraheem Ayoub,Ms. Wesam Dalal Khalaileh 5. The Reality of the Role of Yemeni Public Universities in Cultural Awareness for Their Students During the Al-Aqsa Flood Battle and Ways to Strengthen It from the Perspective of Their Academic Leaders Mr. Abdul-Raqib Qasim Ali Al Sharif 6. The role of professional licensing in developing the performance of general education teachers in the Kingdom of Saudi Arabia: opportunities and challenges Ms. Samia Abdulrahman Alrifai 7. The effect of students dropping out of secondary schools on their cognitive outcome and attitude towards learning from the point of view of their teachers Mr. Ayoub Suleiman Salama Al-Qarinawi ,Mr. Badi Aziz Al-Qashala 8. Cyberbullying and its relationship to negative thinking among Hail University female students Ms. Ashwag Fayz Al-Rashed, Prof. Benayan Bani Al-Rashedy